A Novel Nontraumatic Gingival Retraction Method for a Single-Unit Crown Impression - Hozaifa Al-Nasser; Nabil Al-Houri; Anas Mouti; Heba Alajami (Case Reports in Dentistry)
Until now, there have been three traditional options for gingival retraction procedures, mechanical, chemicomechanical, and surgical methods, which have a degree of trauma that varies according to the clinical experience. The gingival tissue may be very delicate and susceptible to recession if too much trauma was applied. This article describes a novel nontraumatic gingival retraction method, without cords, chemicals, surgery, or any special equipment.